Strain Distribution Equal Channel Angular Pressing of Magnesium alloy at 90° and 120° Corner Angles - Samsudin, M.; Kurniawan, Denni; Nor, F. (2015)
© 2015 Severe plastic deformation (SPD) is capable of producing metals with ultrafine grained microstructure. Equal channel angular pressing (ECAP) is a type of SPD process and is the focus of this study. The process was simulated using finite element analysis at different channel angles of 90° and 120°. The input for material properties, loads, velocities, boundary conditions and contacts were assigned to the finite element models to simulate the process. The strain distribution value were be obtained from the finite element analysis to determine the effect of the channel angle to the magnesium alloys AZ80 sample. The result shows that when the channel angle was 120°, the strain was lower but the concentrated stress at the corner region of the channel also lowers compared to when the channel angle was 90°. At any channel angle, presence of corner radius lowers the strain and the stress.